Antinociceptive and anti-inflammatory effect of metformin in experimental models conducted in mice - Sánchez-Gavidia, Joseph (2019)
Objective: To analyze the anti-inflammatory and antinociceptive activity of metformin in an acute event of inflammation-edema and pain induction in rodents. Materials and methods: One hundred ninety-eight (198) female mice were used. The anti-inflammatory effect was evaluated in 64 mice using the carrageenan-induced paw edema test, and the antinociceptive effect was assessed in 64 and 70 mice using the hot plate test and the tail immersion test, respectively. In both cases, there were control, placebo and experimental groups. For the analysis, the Shapiro-Wilk test, one-way ANOVA test, Tukey test and Pearsonian coefficient of correlation were used. Results: In the carrageenan-induced paw edema test, the metformin 50 and 150 mg/kg groups showed an anti- inflammatory effect at the second and third hours. In the hot plate test, the metformin 100, 200 and 250 mg/kg groups showed an antinociceptive effect at the second and fourth hours. In the tail immersion test, the metformin 100, 150, 200 and 250 mg/kg groups showed an antinociceptive effect from minute 15 until the end of the experiment. In addition, the metformin 150 mg/kg group had a statistically equivalent effect to the morphine 10 mg/kg control group. Conclusions: The acute anti-inflammatory and antinociceptive activity of metformin at different doses is demonstrated in experimental models conducted in mice.